Comparing te concept of magic in Harry Potter and the order of the Phoenix ( 2007 ) and Hilmi 'Ali Sya'ban's the tale of moses - Nabilatulfikrah Shanelia Zikri (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/adil,c.1